PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) PADA PT BANK MANDIRI - Vidya Amalia Rismanty; Amthy Suraya (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) at PT Bank Mandiri (Persero) Tbk for the 2012-2021 period. The data used in this study is secondary data sourced from financial report data on the official website of PT Bank Mandiri (Persero), Tbk which is listed on the Indonesia Stock Exchange. In this study using 1 company with a period of 10 years, namely in 2012-2021. This research method uses an associative method with a quantitative approach. The results of this study indicate that the variable X1 shows the Capital Adequacy Ratio (CAR) partially has a negative and significant effect on Return On Assets (ROA) with a tcount (-4.318) > ttable (2.365) and a significant value of 0.003 <0.05. The results of variable X2 show that the Loan to Deposit Ratio (LDR) partially has a positive and significant effect on Return On Assets (ROA) with a tcount (2.475) > ttable (2.365) and a significant value of 0.042 <0.05. Simultaneously the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a significant and significant effect on Return On Assets (ROA) with Fcount (9.332) > Ftable (4.740) and a significant value of 0.011 <0.05.